Implementation of the R1N1 Program as an Innovative Strategy to Enhance Healthcare Access and Effectiveness in Surabaya through the Integration of Healthcare Personnel and Ambulance Facilities in Every Urban Village - Suhadi Nuryanto; Ika Devy Pramudiana; Sapto Pramono (International Journal of Humanities and Social Sciences Reviews, 2025)
This study aims to analyze the implementation of the R1N1 Program as an innovative strategy to improve access and the effectiveness of healthcare services in Surabaya through the integration of healthcare personnel and ambulance facilities in each subdistrict. The program is measured using Everett Rogers' Diffusion of Innovation theory with five main indicators: Relative Advantage, Compatibility, Complexity, Trialability, and Observability. The research method used in this study is a qualitative approach, with data collection through in-depth interviews with various stakeholders, such as medical personnel, government officials, and the community. The results show that the R1N1 Program has successfully had a positive impact on improving healthcare access, with an observability rate of 90% and a relative success rate of 80%. The community has directly experienced the benefits of this program, particularly in reducing medical service waiting times. However, challenges remain related to coordination between medical staff and ambulances, as well as the limited understanding of the community regarding operational procedures. In conclusion, while the R1N1 Program has shown significant success, improvements are needed in coordination, socialization, and more stable funding support to ensure the sustainability and expansion of this program throughout Surabaya.